Relación entre la adicción a las redes sociales y las habilidades sociales en la adolescencia - Arriaran Valdivia, Maria Alejandra (2022)
Currently, the use of social networks has become a relevant aspect in our lives, being one of the most used platforms, since it helps us to have greater connectivity with people around us. However, there are dangers such as impaired social skills when it becomes an addiction. The adolescent population has a higher risk of presenting this type of addiction due to the evolutionary changes it faces. That is why the purpose of this work is to identify the relationship between addiction to social networks and social skills in adolescents. For this, taking into account the PRISMA guidelines, the following databases were used: ProQuest, Ebsco, Dialnet and Scopus, from which 10 articles were selected, whose years of publication range from 2014 to 2021. The results indicate the existence of a statistically significant and inverse relationship between addiction to social networks and social skills; as well as the presence of a negative and significant relationship between social skills and addictive use of networks; Finally, adolescents with a lower repertoire of social skills have a tendency to pathological use of social networks.